Pertanggungjawaban Hukum Para Pihak Perjanjian Elektronik P2P Lending dalam Kasus Pembobolan Dana Kredit Shopee Paylater - Belva Rajendra; Kukuh Tejomurti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The development of technology-based peer-to-peer financing services (LPBBTI) in Indonesia, including platforms like Shopee Paylater, has facilitated easier access to credit. However, this progress is accompanied by cybersecurity risks, such as unauthorized use and account breaches. This study aimed to (1) analyze the operation of LPBBTI under prevailing regulations, and (2) examine the legal liability of parties in cases of Shopee Paylater credit breaches.The study employed a normative legal approach with prescriptive characteristics, combining statutory, conceptual, and case-based analyses. Primary and secondary legal materials were obtained through literature review of Law No. 8 of 1999, POJK No. 10 of 2022, POJK No. 40 of 2024, and personal data protection regulations. The analysis was conducted descriptively and qualitatively. The findings indicate that, despite OJK regulations, Shopee Paylater’s electronic agreements still contain standard clauses that unilaterally shift all account security risks to users. This practice potentially violates Article 18(1)(a) of the Consumer Protection Law and is void under Article 18(3). Consequently, consumers remain liable for payments even if transactions are conducted illegally by third parties. In line with Article 19 of the Consumer Protection Law, service providers should assume liability, as system security is under their control.